ANALISIS KESULITAN BELAJAR MATEMATIKA SISWA KELAS 3 SD N 2 DONOTIRTO KRETEK BANTUL YOGYAKARTA - Ida Ayu; Siti Maisaroh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze mathematical learning difficulties seen from difficulties in learning facts, concepts, and operations, as well as to identify factors causing mathematical learning difficulties among students of class 3 SD 2 Donotirto Kretek Bantul. This research is qualitative. The subjects of this study are teachers, students, and parents of III SDN 2 Donotirto students. Data collection methods include interviews and observations. The data analysis activities follow Miles & Huberman's approach, which includes data reduction, data presentation, and initial conclusions, as the analytical techniques used. Source triangulation, particularly interviews with third-grade teachers, children, and parents, is used to assess data validity. Validity checks use triangulation techniques, namely interviews, observations, and documentation. Based on the research results, it was found that (1) Difficulties in learning facts: students struggle to understand and correctly write mathematical symbols, as well as to write thousands and hundreds of thousands of words correctly when instructed by the teacher; (2) Difficulties in learning concepts: students cannot yet distinguish between the numerator and denominator in fractions, students experience difficulties when faced with story problems in arithmetic operations, students still cannot interpret these story problems, and students do not understand the definitions and characteristics of flat shapes; (3) Difficulties in learning operations: students have difficulties solving division arithmetic operations. Low interest and attitudes towards learning are contributing factors to students' learning difficulties, and teachers rarely or never use teaching media during lessons.